Fluorescence studies on new potential antitumoral 1,3-diarylurea derivatives in the thieno[3,2-b]pyridine series encapsulated in magnetoliposomes - Rodrigues, Ana Rita O. (2012)
Magnetic nanoparticles of magnetite and of nickel core with silica shell were prepared and either covered with a lipid bilayer or entrapped in liposomes, forming magnetoliposomes. New potential antitumoral 1,3-diarylurea derivatives of thieno[3,2-b]pyridines were then encapsulated in liposomes and magnetoliposomes and their photophysical behavior was investigated.